Metode Kritik Abu Hafs Umar Bin Ali Al-Basri Al-Fallas Terhadap Para Perawi Hadis - Masruri, Ulin Niam (RIWAYAH, 2015)
Activities  of hadith criticism have already been running  in the era of the Prophet. However, the criticisms are still very limited. In the next period, this activity develops after an unstable political and social conditions after the murder of Caliph Us}ma>n bin Affa>n in the year 36 H. The experts increasingly sharpen criticism of hadith narrators to fortify the traditions of counterfeiting of people who seek profit in order political interests. This article discusses the critic figure Imam al-Falla> s in criticizing the narrator of traditions with an objective approach so that the hadith experts who live afterwards make it as a reference. And, not surprisingly, Imam Bukhari narrated the hadith through him.